GAMBARAN SIKAP PASIEN ASMA MENGENAI KEGIATAN OLAHRAGA DALAM PENCEGAHAN SERANGAN ASMA - Cucu Ernawati; Sansri Diah KD; Yati Tursini; Yosep Rohyadi (Politeknik Kesehatan Kemenkes Bandung, 2020)
This research is motivated by the increasing asthma incidence in the city of Bandung. Asthma is a chronic disease that needs to be managed pharmacologically and non-pharmacologically. One of the non-pharmacological management is sports activities. Exercise can strengthen the breathing muscles in asthma patients. Not all asthma patients have high enthusiasm to exercise, depending on how the patient's attitude. An attitude is needed to provide a response that can start or guide sports behavior. This study aims to identify the attitude of asthma patients regarding sports activities in the prevention of asthma attacks. This study included a qualitative, research design using a descriptive design with systematic literature review method through searching journals in Google Schoolar with keywords asthma patient attitudes towards sports in preventing asthma recurrence so that 4 journals were obtained based on the characteristics of respondents, places, and methods. The results of the 4 journals included recurrence prevention efforts as much as positive 76.5% and negative 23.5%, family attitudes in preventing recurrence of asthma were good (positive) 89.6% while less (negative) categories were 10.4% , asthma patients who have a positive attitude towards asthma and gymnastics as much as 52.9% while those who are negative 47, 1%, and negative perceptions about preventing asthma recurrence by 56% while positive perception 44%. Conclusions from 4 journals found that most asthma patients are positive about exercise in preventing asthma attacks. It is hoped that health workers will increase their role regarding exercise in preventing asthma attacks and further research related to behavior in preventing asthma attacks.